The Issues of Track Maintenance Management in Indonesia (Based on Study of the British Railways) - Tetria Yunik Dewi Pamungkas; Imam Muthohar (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2017)
It is believed that there is merit in researching how the management of track maintenance is organized in the United Kingdom, in particular by Network Rail, and then evaluating how this can be applied to the benefit of Indonesian Railways. The purpose of this research was expected to provide recommendations for management improvement of track maintenance by researching the track maintenance management system in Network Rail. This research study is based on secondary data. The analysis was conducted by using comparison method which compares the British Railways management and Indonesia railway management related to track maintenance management. The track maintenance management system was studied by using Network Rail. The results were compared with track maintenance management system in Indonesia. The comparison will provide the data differences that evaluated so the problem can be identified. The final result of this analysis was the identification of problems and improvisation that can be done for the development of track maintenance management in Indonesia. Several management issues have been mapped to several groups: finance management, structure organization, and asset management. From the problems that have been mapped, some improvements are recommended as monopolist authority restriction, maintenance system contract extension, re-structuring organization hierarchy, business plan consideration, track monitoring strategy arrangement, and condition based maintenance strategy adoption.